2012
DOI: 10.7448/ias.15.2.18020
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to linkage to ART in primary care: a qualitative study of patients and providers in Blantyre, Malawi

Abstract: IntroductionLinkage from HIV testing and counselling (HTC) to initiation of antiretroviral therapy (ART) is suboptimal in many national programmes in sub-Saharan Africa, leading to delayed initiation of ART and increased risk of death. Reasons for failure of linkage are poorly understood.MethodsSemi-structured qualitative interviews were undertaken with health providers and HIV-positive primary care patients as part of a prospective cohort study at primary health centres in Blantyre, Malawi. Patients successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
91
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 32 publications
9
91
0
Order By: Relevance
“…Late ART initiation may also reflect the challenges encountered in timely treatment initiation including regular follow-up of pre-ART patients and health system delays. Reasons for delays in ART initiation among adults include distance and cost, prolonged adherence preparation and patients’ unwillingness to initiate treatment [20-22], but factors specific to youth have not been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Late ART initiation may also reflect the challenges encountered in timely treatment initiation including regular follow-up of pre-ART patients and health system delays. Reasons for delays in ART initiation among adults include distance and cost, prolonged adherence preparation and patients’ unwillingness to initiate treatment [20-22], but factors specific to youth have not been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Malawi found that progression through the HIV care pathway, including TB care for co-infected patients, was strongly influenced by socio-cultural norms [20]. Among these norms is particularly the need for the patient to remain respected despite one's declining health.…”
Section: Discussionmentioning
confidence: 99%
“…77,82,85,91,92 Disclosure to friends and family enables patients to access the psychosocial and material support crucial for initiating and staying on treatment. 78,85,88,91,92 …”
Section: Linkage To Care and Treatmentmentioning
confidence: 99%
“…74,75,77,81,88,93 Other studies have found negative provider attitudes and lack of confidentiality to be barriers to initiation. 77,78,88,91 …”
Section: Linkage To Care and Treatmentmentioning
confidence: 99%